On generalized intuitionistic fuzzy subhyperalgebras of Boolean hyperalgebras - Hila, Kostaq; Onar, Serkan; Ersoy, Bayram Ali; Davvaz, Bijan (SPRINGER, 2013)
This paper deals with a special class of hyperalgebra, called Boolean hyperalgebra, which is redefined in it. We introduce the concepts of generalized intuitionistic fuzzy subhyperalgebras and generalized intuitionistic fuzzy hyperideals of Boolean hyperalgebras. A necessary and sufficient condition for an intuitionistic fuzzy subset of the Boolean hyperalgebra to be a generalized intuitionistic fuzzy subhyperalgebra (hyperideal) is proved. Images and inverse-images of generalized intuitionistic fuzzy subhyperalgebra (hyperideal) under Boolean hyperalgebra homomorphism are studied.
Keywords: Boolean hyperalgebra; generalized intuitionistic fuzzy subhyperalgebra; generalized intuitionistic fuzzy hyperideal; generalized intuitionistic fuzzy quotient Boolean hyperalgebra; ALGEBRAS; Mathematics